Protective role of germinated mung bean against progression of non‐alcoholic steatohepatitis in rats: A dietary therapy to improve fatty liver health. Issue 5 (25th March 2018) - Alshammari, Ghedeir M.; Balakrishnan, Aristatile; Chinnasamy, Thirunavukkarasu
Abstract: The current research was focused at investigating the different doses of germinated mung bean (GMB) ( Vigna Radiata [Fabaceae]) on progression of non‐alcoholic steatohepatitis (NASH) from steatosis. Beneficial effects of GBM against NASH from steatosis‐induced liver injury were apparent from decreased serum transaminase activities, lipid peroxidation and nitrite/nitrate contents, and recoupment of glutathione. Enzymatic antioxidants were inclined toward normal in high dose GMB supplemented rats. On the other hand low dose of GMB prevented further alteration when compared with steatosis. Gene expression analysis shows that supplementation of GMB restores the antioxidant enzyme gene expressions. GMB effect was confirmed through histopathological observation, which is correlated along with lipid reduction and various inflammatory cytokine restoration. Further GMB could abrogate alleviated mitochondrial ROS generation. In summary, GMB has a huge potential to decrease the consequence of oxidative stress, which could be one of the contributing mechanism to its protective effect in attenuating the progression of NASH. Practical applications: Mung bean is widely consumed world‐wide by all the population. Germinated mung bean prevents development of steatohepatitis from steatosis. Higher consummation may be recommended for their betterment of liver health.